Análisis de la situación actual del e-commerce de los supermercados que afecta la experiencia de compra del consumidor en Lima Metropolitana - Torres León, Milagros Stefania (2022)
The following study aims to: Establish the current situation of e-commerce in supermarkets and the strategies to follow for its development that affect the consumer shopping experience of Metropolitan Lima. The methodological design of the research was based on a qualitative, descriptive approach. For its part, the sample was made up through probabilistic convenience sampling, being established by 385 people from Metropolitan Lima. The data collection instrument of a survey containing elements that identify the research variable, the statistical techniques for the processing of The information was based on the statistical analysis of the information through the SPSS v.25 program, presenting the results through frequency tables for better understanding. The main findings of this research corroborate that: Regarding how the current situation of e-commerce in supermarkets affects the shopping experience of consumers in Metropolitan Lima, 45.7% of those surveyed indicated that the current situation greatly affects their shopping experience. purchase and 29.6% indicated that it affects their shopping experience too much. Therefore, the current situation due to the pandemic has determined that they use the e-commerce of supermarkets to purchase their product, thus avoiding the spread of the virus and contagion for themselves and their families. In the same way, this correlation was demonstrated by applying the Pearson correlation statistic where a very high positive influence was obtained, since its value r = 0.948, which shows that the current situation of e-commerce in supermarkets affects the experience of purchase of the consumers of Metropolitan Lima.